Evaluación sanitaria en toros de fomento del departamento de Cundinamarca, 1. Estudios bacteriológicos. - Gallego Marín, Manuel I.; Cortés Castillo, Esperanza; Hernández de Galvis, Alba Lucia; Rozo, Jorge; Villalobos, Rafael (Instituto Colombiano Agropecuario - ICA, 2018)
Ganadería bovina